Numerical Investigation of Flat Plate Solar Collector by Using Various Types of Mono and Hybrid Nanofluids - Karrar A. Al-shibli (International Journal of Intelligent Systems and Applications in Engineering, 2025)
The performance of traditional fluids in heat transmission might be greatly enhanced by using nanofluid, a cutting-edge fluid. Improving the design elements and the convection heat transfer coefficient between the fluid and absorber tubes are the most important ways to raise the solar collector’s overall efficiency. In solar collectors, water nanofluids such as MWCNT, Al2O3, TiO2, SiO2, and CuO are most commonly used nanofluids. This study used controlled conditions to numerically examine the thermal efficiency of flat plate solar collectors using Al2O3, MWCNT, and hybrid Al2O3+MWCNT (80:20%) as a working fluid. The efficiency is examined in relation to a number of characteristics, such as the volumetric flow rate and the volume percentage of nanoparticles, and the intensity of solar radiation. Six concentrations ratio of different nanoparticles were used (0, 0.01, 0.02, 0.03, 0.04, and 0.05) during this numerical investigation, with each of these concentrations six different mass flow rate were used (0.004167, 0.08334, 0.0125, 0.01667, 0.03334, and 0.05) kg/s. The results showed that the highest efficiency was obtained from using MWCNT/water as a nanofluid (76.8%, 78.3%, and 80.4%) at mass flowrate 0.05 kg/s for concentration ratios (0.03,0.04, and 0.05) respectively. While the base fluid (water) at the same mass flow achieved lower efficiency 53.4%. Al2O3/water achieved median efficiency (59.1%, 60.1%, and 61.1%) at mass flowrate 0.05 kg/s for concentration ratios (0.03,0.04, and 0.05), respectively. The efficiency of hybrid Al2O3+MWCNT (80:20%) at mass flowrate 0.05kg/s were 75.2%, 76.5%, and 78.3% for concentration ratios (0.03,0.04, and 0.05) respectively.